VD_FINDINFO Jug / 2012 / 209 vom 2. April 2012 - VD Tribunal cantonal (2012)
PEINE PÉCUNIAIRE, FIXATION DE LA PEINE, DISPOSITIONS PÉNALES DE LA LCR, RÉVOCATION DU SURSIS | 34 CP, 46 CP, 47 CP, 90 ch. 2 LCR